ANALISIS HUKUM PELAKSANAAN HAK INDIKASI GEOGRAFIS KOPI ARABIKA TORAJA: LEGAL ANALYSIS OF THE IMPLEMENTATION OF RIGHTS TO GEOGRAPHICAL INDICATIONS OF TORAJA ARABICA COFFEE - Stakhis, Handriwan; Almusawir; Juliati (Faculty Of Law Bosowa University, 2021)
The research aims to review: 1) The implementation of the book the requirements the right of Geographical Indications Arabica Toraja Coffee barriers; 2) The implementation of the right of Geographical Indications Arabica Toraja Coffee. Research methods that were used normative and empirical research by Using the survey questionnaire. The result showed: 1) The Geographical Indications Arabika Toraja Coffee of production, the use of a sign, keterunutan code, product marketing, and Geographical Indications at an institute of MPIG-Arabica Toraja Coffee. An indication of the right but has not yet been fully implemented by the community protection of Geographical Indications as Arabica Toraja Coffee. 2) The obstacles in the implementation of the Geographical Indications Arabica Toraja Coffee is production process processing and the use of a Geographical Indication in packaging, this is because the supporting infrastructure for the standardization process is not yet available, Arabica Toraja Coffee to the obstacles to the Geographical Indications yet understood the adequate and there is not yet the local government Toraja procedures governing the book the terms of the farmer groups, and the field counselors.